2003
DOI: 10.1385/endo:22:2:161
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Decreases Chemokine Levels in Murine Mammary Tissue: Implications for the Regulatory Role of MIP-1 Alpha and MCP-1/JE in Mammary Tumor Formation

Abstract: Estrogen contributes to the development of breast cancer through mechanisms that are not completely understood. Estrogen influences the function of immune effector cells, primarily through alterations in cytokine expression. Chemokines are proinflammatory cytokines that attract various immune cells to the site of tissue injury or inflammation, and activate many cell types, including T lymphocytes and monocytes. As an initial step toward ultimately determining whether regulation of chemokine expression and/or b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…The best ER-sensitive splicing event was found in FANCA, which is regulated by steroid hormone (51). Two other ER-sensitive ASEs were found in MCL-1 and CCL4 that are tamoxifen and estrogen target genes, respectively (52,53). Notably, it was recently shown that estrogen, ER, and its coregulators can affect the alternative splicing of their target genes (54).…”
Section: Discussionmentioning
confidence: 99%
“…The best ER-sensitive splicing event was found in FANCA, which is regulated by steroid hormone (51). Two other ER-sensitive ASEs were found in MCL-1 and CCL4 that are tamoxifen and estrogen target genes, respectively (52,53). Notably, it was recently shown that estrogen, ER, and its coregulators can affect the alternative splicing of their target genes (54).…”
Section: Discussionmentioning
confidence: 99%
“…Another potential mechanism affecting both T cells and APC is the homing of T cells to lymph nodes and APC from the FRT to the draining lymph nodes. Estradiol reduces expression of chemokine receptors CCR2 and CXCR3, as well as reducing migratory activity in response to MIP-1␣ and MCP-1 (59).…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen has pleiotropic effects, especially on cells of the immune system, and it can inhibit B cell development (54 -56), induce thymic atrophy (57), reduce developing T cell populations (58), induce monocyte apoptosis (59), and inhibit DC differentiation (60). Estrogens increase the production of biologically active TGF␤ from uterine epithelial and vaginal cells, and anti-TGF␤ Abs ablate the estradiol-induced suppression of Ag presentation by rat vaginal cells to CD4 ϩ T cells (34,61).…”
Section: Discussionmentioning
confidence: 99%
“…However, estrogen reduces the levels of MCP-1 in human coronary artery endothelial cells (HCAECs) (86). Estrogen significantly increased the levels of some specific chemokines such as MIP-1a and MCP-1/JE in mammary cells in vivo and in vitro (87), while the expression of chemokines MCP-1/JE and MIP-1a did not change in murine monocytes co-cultured with estrogen or tamoxifen (88). A study has found that both estrogen and tamoxifen significantly down-regulate the expression of CCR2 by murine monocytes and that they downregulate the expression of CXCR3 by murine monocytes to a lesser extent at the same time (88).…”
Section: Chemokinesmentioning
confidence: 99%
“…Treatment with estrogen or raloxifene and tamoxifen was ineffective at changing levels of MCP-1 expression in human umbilical vein endothelial cells (HUVECs) (86). In cultured mammary cells and murine mammary tissue, estrogen significantly down-regulates the levels of specific chemokines -MIP-1a and MCP-1/ JE -compared to baseline levels, and estrogen also suppresses expression of JE/monocyte chemoattractant protein 1(MCP-1/JE) mRNA in murine macrophage cells (87). A study by Janis et al reported no change in the expression of the chemokines MCP-1/JE and MIP-1a in murine monocytes, regardless of whether those cells were co-cultured with estrogen or tamoxifen (88).…”
Section: The Mechanism By Which Estrogen Modulates Chemokinesmentioning
confidence: 99%